A CIM framework for standard-based system monitoring using nagios plug-ins - Lorenzati, Marcelo (2009)
The Common Information Model is a widely-accepted industry standard to model distributed system objects as well as their behaviors and interactions to realize system management tasks. It is endorsed by the Distributed Management Task Force and appears as the preferred manageability solution to deal with the ever increasing heterogeneity characterizing today’s datacenters. However, a number of enterprise-class system management products, like Nagios, are not compliant with this standard. Nagios is among the top open source monitoring tools with the power of a large community of developers producing plug-ins to manage a variety of enterprise systems. As part of the endeavor to accelerate CIM adoption, an extension framework, called Plugin Extension for CIM, has been developed in order to expose Nagios and other third-party plug-ins thru CIM, thus enhancing the capabilities of standard-based system management tools by the transparent use of the extensive variety of existing plug-ins. This paper describes the developed framework as well as its acceptance within the open source manageability community.